APPLICATION OF PROJECT BASED LEARNING TO IMPROVE SECONDARY SCHOOL STUDENTS' CRITICAL THINKING SKILLS - Yance Manoppo; Suyuti Suyuti (CV. ADIBA AISHA AMIRA, 2025)
The aim of this research is to analyze the application of project-based learning (PjBL) in improving secondary school students' critical thinking skills based on a literature review. Critical thinking is an essential skill in 21st century education that allows students to analyze, evaluate and solve problems systematically. However, conventional learning methods are often less effective in developing these skills. This research uses a qualitative method with a literature review approach (library research), by examining various scientific sources such as academic journals, books, conference proceedings and research reports in the last 10 years. The results of the study show that PjBL has high effectiveness in improving students' critical thinking through a process of exploration, problem solving and collaborative work. The main factors that contribute to the success of PjBL include relevant project design, active student involvement, and support from teachers and learning facilities. However, the implementation of PjBL still faces challenges, such as limited time in the curriculum, lack of teacher training, and limited resources in some schools. As a recommendation, training is needed for teachers regarding the implementation of PjBL, flexibility in the curriculum to support project-based learning, and the use of technology as a learning tool. With the right strategy, PjBL can be an effective learning method in equipping students with the critical thinking skills needed in the academic and professional world.